National Policy on China One Belt-One Road (OBOR) Initiative Towards Indonesia as Global Maritime Nexus - Riko Ratna Setiawan; Muhammad Kamil (Faculty of Social and Political Sciences, Universitas Muhammadiyah Malang, 2021)
One Belt-One Road Initiative is a huge project that is still a subject of discussion in the world. The project initiated by the Chinese state invites cooperation with various countries in the world in order to reactivate the maritime silk route, including Indonesia. There are 5 pillars of OBOR which are strengthening connectivity, improving infrastructure, promoting trade and scurity, increasing monetary circulation and increasing public understanding of maritime cooperation. There are some indonesian political experts argue that this cooperation will be dominated by China in all five pillars, which in the end will only make Indonesia “an instrument